Trademark Registration Incentive Regulation for Small Businesses in Tourism: Human Rights and Protection Systems Comparison - Samsithawrati, Putu Aras; Dharmawan, Ni Ketut Supasti; Putra, Made Aditya Pramana; Sawitri, Dewa Ayu Dian; Hong, Tan Jian (Jurnal Suara Hukum, 2025)
This study aims to compare trademark protection systems adopted in Indonesia and Malaysia on exclusive rights to trademarks, especially in the human rights context, and to analyze regulations in both countries in supporting small business in the tourism sector through trademark registration incentives. The normative legal research method is used in this study by using statutory, conceptual, and comparative approaches with descriptive qualitative analysis. The study reveals that trademarks as intangible property rights and the right to own property can be considered human rights refer to Arts. 27(2) and 17 UDHR. To strengthen trademark protection in human rights and Intellectual Property Rights contexts, Indonesia adopts a first-to-file system where trademark registration is an obligation, because it protects those who file it first, as stipulated in Law No. 20 of 2016. Gianyar as tourism area in Bali-Indonesia has Regent Regulation Number 86 of 2021 that supports small businesses in tourism through trademark registration incentives. Meanwhile, Malaysia adopts a first-to-use trademark protection system stipulated in the Trademark Act 2019.  However, trademark registration is an essential step to ensure business continuity. Both Indonesia and Malaysia governments have at least attempted to play a positive role in supporting the growth of their economies.